Experimental and numerical study on the performance of passive heat sink having alternating layout. (June 2019) - Chu, Wen-Xiao; Lin, Yu-Chieh; Chen, Ching-Yao; Wang, Chi-Chuan
Highlights: A novel passive heat sink with triangular fins having alternating layout is proposed. Five designs are investigated through experimental and numerical studies. The novel heat sink can entrain more airflow and also has a higher view factor. The heat transfer coefficient (HTC) can be improved by up to 13.0% in vacuum and 14.6% in atmosphere. HTC can be improved further by 20.3% for triangular fins having alternating layout with 150° angle. Abstract: In this study, a novel passive heat sink with triangular fins having alternating layout to promote heat transfer performance of a passive heat sink is proposed and verified by experimental and numerical examinations. The heat sinks with rectangular fins (case A ), triangular fins with right angle, 90° (case B ), triangular fins with right angle having alternating layout (case C ), triangular fins with obtuse angle of 120° (case D ) and triangular fins with obtuse angle of 120° having alternating layout (case E ) are tested with vacuum pressure ranging from 400 Pa to atmosphere pressure. It is indicated that the triangular fin having alternating layout offer some benefits like entraining more airflow into the heat sink and a higher effective view factor, thereby showing an appreciable increase of effective heat transfer coefficient (HTC). Results obtained in low vacuum pressure show that the effective HTC of cases B, C, D and E can be improved by 1.5%, 5.5%, 3.0% and 12.1%, respectively as compared to the reference case A . Yet the effective HTC can be improved by 3.2%, 6.1%, 4.6% and 13.0%, respectively in atmosphere pressure. The numerical study is in line with the experimental results and the simulations suggest that the optimum angle of the proposed triangular fins having alternating layout can improve the effective HTC by up to 14.6% and 16.0% with obtuse angles of 150° and 140° when fin area is 2000 mm 2 and 3000 mm 2, respectively. The benefits of triangular fins having alternating layout show even more superior performance when the heat sink is placed vertically and the effective heat transfer coefficient for triangular fins having alternating layout with 150° is improved by up to 20.3%.